SAT0515 Clinical characteristics of patients with cancer-associated myositis complicated by interstitial lung disease. (12th June 2018) - Kaneko, Y.; Nunokawa, T.; Taniguchi, Y.; Yamaguchi, Y.; Gono, T.; Masui, K.; Kawakami, A.; Kawaguchi, Y.; Sato, S.; Kuwana, M.; ,
Abstract : Background: Cancer-associated myositis (CAM) is believed to be rarely complicated by interstitial lung disease (ILD), and, thus, detailed clinical characteristics of CAM in patients with polymyositis (PM)/dermatomyositis (DM)-associated ILD are not well known. Objectives: To clarify the incidence, risk factors, and impact on survival of malignancy in patients with PM/DM-associated ILD, using a large cohort data. Methods: We used 497 patients with PM/DM-associated ILD enrolled in a multicentre retrospective cohort of incident cases from 44 institutions across Japan (JAMI). CAM was defined as malignancy diagnosed within 3 years before or after PM/DM diagnosis. Demographic data and clinical characteristics were recorded at the time of diagnosis, and follow-up survival and malignancy data were collected prospectively. Results: Thirty-two patients with CAM (6.4%) were identified. Patients in the CAM group were older (64.3 vs 55.1 years, p<0.001), had shorter disease duration at onset (4.1 vs 7.0 months, p=0.01), and presented with arthritis less frequently (24.1 vs 48.5%, p=0.01), in comparison with those with non-CAM group. All patients with CAM were older than 40 years, and the proportion of CAM increased along with the age. Patients who were ≥59 years at diagnosis and lacked arthritis were at 12 times higher risk for concomitant malignancy than those without such features (figure 1). Frequencies of autoantibodies, including anti-MDA5, anti-ARS, and anti-TIF1gamma, were not different between the groups. In 19 patients (59%), malignancy was diagnosed within 3 months before or after PM/DM diagnosis. Eleven CAM patients were died, and cause of deaths included ILD in 6 and malignancy in 5. Survival analysis by Kaplan-Miere method demonstrated that CAM patients had a poorer survival than did non-CAM patients (p=0.016). Conclusions: In patients with PM/DM-associated ILD, older age at diagnosis and lack of arthritis are predictors for concomitant malignancy, which leads to a reduced survival. Disclosure of Interest: Y. Kaneko Speakers bureau: Astellas, T. Nunokawa: None declared, Y. Taniguchi: None declared, Y. Yamaguchi: None declared, T. Gono: None declared, K. Masui: None declared, A. Kawakami: None declared, Y. Kawaguchi: None declared, S. Sato Grant/research support from: a patent on anti-MDA5 antibody-measuring kit, M. Kuwana Grant/research support from: Astellas, Speakers bureau: Astellas, Japan Blood Products Organisation, Medical and Biological Laboratories